Penggunaan E-LKPD Berbasis Pembelajaran STAD untuk Meningkatkan Kemampuan Hasil Belajar Menulis - Nur Alfin Hidayati; Agus Darmuki (Universitas PGRI Semarang, 2022)
This research is motivated by the low value of writing learning outcomes for fifth grade students at SDN Margorejo Surabaya in the 2021/2022 academic year. The purpose of this research is to describe the improvement of writing ability using electronic student worksheets based on STAD learning in fifth grade students of SDN Margorejo. This research is a classroom action research using a 2 cycle design. Each cycle consists of planning, implementation, observation and reflection. The object of this research is the writing learning process for the fifth grade students of SDN Margorejo, totaling 30 students with details of 11 males and 19 females. Data collection techniques using observation sheets, documentation and tests. The data analysis technique used data triangulation. The results showed an increase in writing ability using STAD learning-based electronic student worksheets from the pre-cycle average score of 62 to 74 in cycle 1 and increased to 89 in cycle 2. learn to write for fifth graders at SDN Margorejo Surabaya in the 2021/2022 academic year.